2015
DOI: 10.18632/oncotarget.6516
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin-mediated inhibition of PI3K/AKT/mTOR axis and anticancer activity in non-small cell lung cancer cells

Abstract: Auranofin, a gold complex that has been used to treat rheumatoid arthritis in clinics and has documented pharmacokinetic and safety profiles in humans, has recently been investigated for its anticancer activity in leukemia and some solid cancers. However, auranofin's single agent activity in lung cancer is not well characterized. To determine whether auranofin has single agent activity in lung cancer, we evaluated auranofin's activity in a panel of 10 non-small cell lung cancer (NSCLC) cell lines. Cell viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
86
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 57 publications
4
86
0
2
Order By: Relevance
“…AF inhibits expression and phosphorylation of major effectors of the PI3K/AKT/mTOR pathway1718. In this study, our data support a novel conceptual model in which we identify vulnerabilities in wild type EGFR NSCLC cells following treatment with the TUSC2-erlotinib combination which we found could be targeted with the repurposed drug AF.…”
supporting
confidence: 71%
“…AF inhibits expression and phosphorylation of major effectors of the PI3K/AKT/mTOR pathway1718. In this study, our data support a novel conceptual model in which we identify vulnerabilities in wild type EGFR NSCLC cells following treatment with the TUSC2-erlotinib combination which we found could be targeted with the repurposed drug AF.…”
supporting
confidence: 71%
“…The PI3K/AKT/mTOR signaling pathway is a main signaling pathway to regulate cell growth, proliferation, metabolism and survival, commonly deregulated in cancer [30]. Alterations of the PI3K/AKT/mTOR signaling pathway occur at multiple levels, leading to PI3K activation and malignant transformation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Trypanothione reductase of L. infantum (Ilari et al, 2012) revealed, albeit at low resolution, evidence for Auranofin’s tetra-acetyl-thio-glucopyranoside moiety binding to the trypanothione binding site, suggesting interference with the substrate as another possible mechanism of inhibition. Dual inhibition of inflammatory and redox pathways by Auranofin makes it a promising candidate for new applications as an anti-cancer agent (Li et al, 2015; Topkas et al, 2015; You and Park, 2015) and in treating of parasitic infections in humans (Debnath et al, 2012a; Madeira et al, 2012; Tejman-Yarden et al, 2013). …”
Section: Introductionmentioning
confidence: 99%